(untitled) (The Journal of Psychology and Sociology, 2014)
This paperexamines the mainapproaches to the analysisof modelsof disability.In particular, it is not- edthat the basis forselectionof modelsof disabilityaredisabilityparadigm: the traditional, ormedicaland- postconventional, orsocial. Particular attentionis drawn to themodel of disabilityallocatedby British and Americanresearchers.